Engineering the T6SS of Pseudomonas for targeted delivery of antibacterial and antifungal effectors - Pérez-Lorente, Alicia Isabel; Araujo-Garrido, Mario; De-Vicente-Moreno, Antonio; Romero-Hinojosa, Diego Francisco; Molina-Santiago, Carlos (BMC Springer Nature, 2025)
Background Bacteria employ diverse molecular systems, such as the type VI secretion system (T6SS) to outcompete other microorganisms and adapt to ecological niches. The T6SS is a versatile nanomachine capable of delivering toxic effectors into neighboring cells, providing advantages in bacterial interactions. In recent years, T6SSs have been proposed as promising tools for engineering selective antimicrobial platforms. Results In this study, we successfully engineered Pseudomonas putida KT2440 to heterologously express and release T6SS effectors. The expression of Tse1, an effector from Pseudomonas chlororaphis, induced sporulation in plant-beneficial Bacillus strains via a T6SS-dependent mechanism, particularly when Tse1 was paired with a PAAR protein. Similarly, the engineered strain effectively inhibited Aeromonas hydrophila growth using the phospholipase toxin TplE from Pseudomonas aeruginosa. Furthermore, antifungal activity was achieved by coexpressing Tfe2, an effector from Serratia marcescens, with VgrGs, resulting in increased reactive oxygen species levels and cellular damage in Botrytis cinerea. Importantly, the T6SS was also employed to deliver non-T6SS effectors such as chitosanase, demonstrating its versatility in degrading fungal cell walls.
Keywords: Pseudomonas; Effectors; T6SS